Tabernacolo Santa Caterina: Valorizzazione del sito del Tabernacolo di Benozzo Gozzoli Legoli, Peccioli (Pisa) - Heliopolis 21 (AND Rivista di architetture, città e architetti, 2019)
The project, winner of an invitation-only competition for the enhancement of the site of the Tabernacle of Santa Caterina frescoed by Benozzo Gozzoli in Legoli, has as its priority objective the creation of new multifunctional space and the recovery and enhancement of the area surrounding the Tabernacle.